2020
DOI: 10.1101/2020.09.13.295493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genes with 5′ terminal oligopyrimidine tracts preferentially escape global suppression of translation by the SARS-CoV-2 Nsp1 protein

Abstract: Viruses rely on the host translation machinery to synthesize their own proteins. Consequently, they have evolved varied mechanisms to co-opt host translation for their survival. SARS-CoV-2 relies on a non-structural protein, NSP1, for shutting down host translation. Despite this, it is currently unknown how viral proteins and host factors critical for viral replication can escape a global shutdown of host translation. Here, using a novel FACS-based assay called MeTAFlow, we report a dose-dependent reduction in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 136 publications
(199 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, the increase in the ratio of intronic to exonic reads was greater in genes whose expression was reduced along infection compared to genes whose expression was induced (Figure 3G and Figure S6A), illustrating the relative increase in intronic reads is mostly independent of newly transcribed RNAs. Finally, we also detected more intronic reads in cells that exogenously expressed NSP1 42 (Figure S6B). Together these results indicate that the increase in intronic reads compared to exonic reads during SARS-CoV-2 infection is largely driven by accelerated degradation of mature cellular transcripts that leads to relative reduction in exonic reads.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the increase in the ratio of intronic to exonic reads was greater in genes whose expression was reduced along infection compared to genes whose expression was induced (Figure 3G and Figure S6A), illustrating the relative increase in intronic reads is mostly independent of newly transcribed RNAs. Finally, we also detected more intronic reads in cells that exogenously expressed NSP1 42 (Figure S6B). Together these results indicate that the increase in intronic reads compared to exonic reads during SARS-CoV-2 infection is largely driven by accelerated degradation of mature cellular transcripts that leads to relative reduction in exonic reads.…”
Section: Resultsmentioning
confidence: 78%
“…Relatively to cellular mRNAs, cytoplasmic lncRNAs were less affected by SARS-CoV-2 infection ( Figure 3C), indicating accelerated turnover of cellular transcripts in infected cells may be related to their translation. Recently, ribosome profiling and RNA-seq were conducted on cells transfected with NSP1 42 . Analysis of the RNA expression from this data revealed that ectopic NSP1 expression leads to weaker but similar signatures to the ones we identified in infected cells; stronger reduction of cytosolic transcripts compared to nuclear transcripts, stronger sensitivity of nuclear encoded transcripts, and stronger reduction of translated mRNA compared to cytosolic lncRNAs ( Figure S5A-C).…”
Section: Cellular Mrnas Are Degraded During Sars-cov-2 Infectionmentioning
confidence: 99%
“…The apparent low translation efficiency of host response mRNAs may be mediated by the SARS-CoV-2 protein nsp1, which was recently reported to associate tightly with the 40S ribosomal subunit as well as non-translating 80S ribosomes to prevent binding of capped mRNA and thus inhibit the formation of the translation initiation complex (Schubert et al, 2020), much like its SARS-CoV counterpart (Narayanan et al, 2015). In addition, there is increasing evidence that ectopic expression of Nsp1 can alter host mRNA translation (Rao et al, 2020). Our study complements these studies and provides the first published evidence on the potential inhibitory effects of Nsp1 on host mRNA translation at biologically relevant infection settings.…”
Section: Discussionmentioning
confidence: 99%
“…First, general cellular translation inhibition generates the large pool of ribosomes necessary to ensure efficient and massive synthesis of viral proteins. Interestingly, the cellular mRNAs coding for protein components of the translational machinery such as ribosomal proteins and translation factors are preserved from the overall translation inhibition presumably in order to maintain a functional translational machinery during viral translation (Rao et al, 2020). Secondly, the cellular translation silencing inhibits more specifically mRNA subsets that are involved in cellular immune responses to viral infection.…”
Section: Introductionmentioning
confidence: 99%